Cultivo do algodoeiro BRS Rubi com água de esgoto doméstico tratado e doses de potássio no semiárido pernambucano - LIMA, Breno Leonan de Carvalho (2018)
In the face of global water scarcity, it is imperative to use alternative sources for less restrictive uses. Cotton farming in the context of family farming is an important agricultural option when dealing with the semi-arid region, due to its adaptation to water scarcity conditions. At the present time, the reuse of wastewater becomes a primordial strategy to address the water shortage problem in the semi-arid region, as well as to obtain high rates of productivity and satisfactory profitability. Potassium is an ion relevant to plants, however, in most Brazilian soils where cotton is cultivated, the reserve of this nutrient is low, and its supply is essential. In view of the above, the effect of irrigation with treated domestic sewage water and potassium doses on the BRS Rubi cotton crop in the semi-arid region of Pernambuco was studied. The experiment was conducted in the Pilot Unit of hydrous reuse of the Federal Rural University of Pernambuco. The treatments were arranged in a factorial (5 x 5) + 1 scheme with 4 replications, in the randomized block design, consisting of five irrigation slides using treated domestic sewage water (50, 75, 100, 125 and 150% ETc) and five doses of potassium (0, 50, 100, 150, and 200% as recommended for the crop) and an absolute control (AC) irrigated with water from a blade supply corresponding to 100% ETc and fertilized with N, P and K. The application of slides with treated domestic sewage and potassic doses increased leaf gas exchange, providing better growth rates, yield and technological quality of the fiber. The 100% ETc slide with treated domestic sewage water promoted gains of 983 kg ha-1 of cotton seed in relation to AC. The use of wastewater provided fibers with desirable characteristics for the textile industry. Therefore, the study reveals a viable alternative source, enabling the cultivation of the colored cotton in the backlands of Pernambuco with the quality of the fiber, meeting the requirements of the national and international textile industry.